2009
DOI: 10.1097/ico.0b013e318190734d
|View full text |Cite
|
Sign up to set email alerts
|

Can We Measure Corneal Biomechanical Changes After Collagen Cross-Linking in Eyes With Keratoconus?-A Pilot Study

Abstract: There were no significant differences in corneal biomechanical properties, as measured with the ORA parameters CH and CRF, after CXL in keratoconus. IOPcc, IOPg, and GAT-IOP values were transiently elevated after CXL treatment in our study. Whether this reflects a measurement artifact resulting from corneal changes or true elevation of intraocular pressure is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 21 publications
8
67
0
2
Order By: Relevance
“…According to international bibliography, our study is among the few ones that attempt to investigate CH and CRF trends after CXL. Similar results were presented by Goldich et al [26] and by Sedaghat et al [27] in a series of ten and 56 eyes respectively, with a follow-up of 6 months. Vinciguerra et al [28] extended the post-operative period to 12 months; however, they recruited only 24 eyes in their report.…”
Section: Discussionsupporting
confidence: 87%
“…According to international bibliography, our study is among the few ones that attempt to investigate CH and CRF trends after CXL. Similar results were presented by Goldich et al [26] and by Sedaghat et al [27] in a series of ten and 56 eyes respectively, with a follow-up of 6 months. Vinciguerra et al [28] extended the post-operative period to 12 months; however, they recruited only 24 eyes in their report.…”
Section: Discussionsupporting
confidence: 87%
“…Very interesting are our findings of biomechanical corneal stability that so far has been evaluated only in patients that underwent epi off treatment [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 95%
“…There were no significant differences in corneal biomechanical properties as measured with the parameters CH and CRF. 15 In another study, Sedaghat et al 16 compared CH and CRF before and after CXL for KC and concluded that although previous in vitro studies found a change in corneal rigidity, their study found no significant change in CH or CHF measured by biomechanical waveform analysis. These results were echoed in a study by Gkika et al, in which no significant change in the CRF parameters were found in keratoconic eyes before and after riboflavin/ UVA corneal CXL.…”
Section: Clinical Evaluation Of the Biomechanical Changes Occurring Imentioning
confidence: 99%